General-compensation-purpose Static var Compensator prototype - Guillardi Junior, Hildo; Liberado, Eduardo Verri [UNESP]; Pomilio, Jose Antenor; Marafao, Fernando Pinhabel [UNESP] (Elsevier B.V., 2019)
Static var Compensator (SVC) has a general topology and its operational principle allows its application with distinct compensation purposes, such as voltage regulation or load balancing. Thus, this paper presents the development of a SVC prototype that could be used to test and validate a variety of control strategies proposed for the SVC applications. These strategies may include distributed/cooperative approaches, since the designed prototype has two control units with independent metering hardware. The design of the analog signal conditioning boards developed for voltage and current measurement is also presented. Design and control methods for reactive compensation under unbalanced and/or distorted voltages or loads are described and validated using the presented prototype. (C) 2018 The Authors. Published by Elsevier Ltd.
Keywords: Static var Compensator; Microgrid; Power measurement; Analog conditioning